Monitoring the ozonation of phenol solutions at constant pH by different methods - Contreras, Edgardo Martin (2011)
In this study the oxidation-reduction potential (ORP) and the proton production (Hp) profiles as a function of time were proposed as indicators to monitor the ozonation of phenol solutions at constant pH. Analysis of the ozone gas outlet stream (XO3), COD, and phenol measurements in the aqueous phase confirm the reliability of the proposed indicators. Results show that the derivative with respect to time of the normalized ozone gas outlet concentration ((1/XO30)dXO3/dt), of the oxidation-reduction potential (dORP/dt) or of its logarithmic value (dLog(ORP)/dt), and of the proton production rate (dHp/dt) exhibited maximum values that were close to the critical ozonation time (tc) determined by XO3, COD, and phenol measurements. Additionally, ORP and XO3 measurements were useful to determine tc for all the tested pHs (5 to 11); however, Hp was useful only for pH values higher than 9. The indicators of the ozonation process proposed in the present work (ORP, Hp) as alternatives of XO3 may be useful to control the addition of ozone, minimizing the ozonation process costs.